2008
DOI: 10.1007/s00125-008-1135-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cardiovascular disease in non-alcoholic fatty liver disease: causal effect or epiphenomenon?

Abstract: Non-alcoholic fatty liver disease (NAFLD), comprising a spectrum of conditions ranging from pure steatosis to steatohepatitis and cirrhosis, has reached epidemic proportions and represents the most common cause of chronic liver disease in the community. The prevalence of NAFLD has been estimated to be between 20% and 30% in the general population, but this value is much higher (∼70-80%) in type 2 diabetic patients, who are also at higher risk of developing advanced fibrosis and cirrhosis. Increasing recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
256
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(282 citation statements)
references
References 61 publications
10
256
1
9
Order By: Relevance
“…In this context, studies have been conducted to determine whether an elevated serum GGT level and fatty liver are predictive of future CVD events. Some studies have examined the impact of elevated serum GGT levels on all-cause and CVD mortality and showed positive results 14,15) , and similar results have been reported regarding the relationship between fatty liver and CVD events 16) . Notably, one study found that the serum GGT levels are significantly associated with all-cause and CVD mortality in men and that this association is stronger among those with increased echogenicity of the liver parenchyma, known as the US sign of fatty liver 17) .…”
Section: Assessment Of Carotid Atherosclerosis and Fatty Liversupporting
confidence: 52%
“…In this context, studies have been conducted to determine whether an elevated serum GGT level and fatty liver are predictive of future CVD events. Some studies have examined the impact of elevated serum GGT levels on all-cause and CVD mortality and showed positive results 14,15) , and similar results have been reported regarding the relationship between fatty liver and CVD events 16) . Notably, one study found that the serum GGT levels are significantly associated with all-cause and CVD mortality in men and that this association is stronger among those with increased echogenicity of the liver parenchyma, known as the US sign of fatty liver 17) .…”
Section: Assessment Of Carotid Atherosclerosis and Fatty Liversupporting
confidence: 52%
“…Only histological examination or proton magnetic resonance spectroscopy ( 1 H-MRS) can quantitatively assess liver fat (more exactly, hepatocellular lipid content) (3,4). Non-invasive algorithms based on metabolic and anthropometric variables, such as the fatty liver index (FLI), lipid accumulation product (LAP), the hepatic steatosis index (HIS) and the Finnish Diabetes Risk Score (FINDRISC) (6,7,8,9,10,11), have been used as a screening test for hepatic steatosis and identify potential patients for further clinical investigation or for epidemiologic studies. They have been applied in various clinical populations to assess prevalence of NAFLD (12) and to provide prognostic information about incident risk of metabolic syndrome and type 2 diabetes, cardiovascular disease and risk of mortality in various sub-groups (13,14,15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Candidates in this respect are low-grade inflammation throughout the body and fatty liver, both of which occur in concurrent obesity. 2,3 The proinflammatory environment that exists in adipose tissue of the majority of obese individuals 4 is thought to precede insulin resistance by enhancing deregulation of adipose tissue, leading to adipocyte cell death. 5 Subsequently, increased amounts of free fatty acids coming from the inflamed adipose tissue reach the liver, where they decrease insulin sensitivity.…”
mentioning
confidence: 99%